Advances in non-coding RNA in tendon injuries - Wang, Bin; Chen, Qiang; Zou, Xiaodi; Zheng, Ping; Zhu, Jie (Frontiers in Genetics, 2024)
Tendons serve as important weight-bearing structures that smoothly transfer forces from muscles to skeletal parts, allowing contracted muscle movements to be translated into corresponding joint movements. For body mechanics, tendon tissue plays an important role. If the tendons are damaged to varying degrees, it can lead to disability or pain in patients. That is to say, tendon injuries have a significant impact on quality of life and deserves our high attention. Compared to other musculoskeletal tissues, tendons are hypovascular and hypo-cellular, and therefore have a greater ability to heal，this will lead to a longer recovery period after injury or even disability, which will significantly affect the quality of life. There are many causes of tendon injury, including trauma, genetic factors, inflammation, aging, and long-term overuse, and the study of related mechanisms is of great significance. Currently, tendon there are different treatment modalities, like injection therapy and surgical interventions. However, they have a high failure rate due to different reasons, among which the formation of adhesions severely weakens the tissue strength, affecting the functional recovery and the patient's quality of life. A large amount of data has shown that non coding 带格式的: 编号方式: 连续 RNAs can play a huge role in this field, thus attracting widespread attention from researchers from various countries. This review summarizes the relevant research progress on non-coding RNAs in tendon injuries, providing new ideas for a deeper understanding of tendon injuries and exploring new diagnostic and therapeutic approaches.The process of reshaping can be divided into different stages, gradually becoming mature after development (20)(18). In the first stage, the cellular tissue undergoes complex transformation, ultimately becoming fibrous tissue. After entering the mature stage, fibrous